The Frankfurt Kitchen: a Case Study for a New Bauhaus and Education (EAAE Annual Conference Proceedings, 2023)
This case study presents a new way to teach design studio based in the case study method employed by the business schools. In the same way the Bauhaus looked for a new way to teach and do architecture this case used the Frankfurt kitchen as a n example to debate things as important nowadays as prefabrication or the role of sociology and gender in architecture.